2021
DOI: 10.1101/2021.08.01.454648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual-level specialisation and interspecific resource partitioning in bees revealed by pollen DNA metabarcoding

Abstract: It is increasingly recognised that intraspecific variation in traits, such as morphology, behaviour, or diet is both ubiquitous and ecologically important. While many species of predators and herbivores are known to display high levels of between-individual diet variation, there is a lack of studies on pollinators. It is important to fill in this gap because individual-level specialisation of flower-visiting insects is expected to affect their efficiency as pollinators with consequences for plant reproduction.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…The ability to identify an individual's entire pollen assemblage results in the valuable characterisation of interactions at varying hierarchical levels throughout a plant-pollinator community [117]. To date, of the studies that have identified resource partitioning within plant-pollinator networks using DNA metabarcoding, all have found that generalised networks or species are made up of specialised individuals [44,84,115,118]. This presents a promising area of research to further investigate the levels of specialisation and generalisation exhibited by pollinators.…”
Section: How Are Resources Partitioned Between Species and Individual...mentioning
confidence: 99%
“…The ability to identify an individual's entire pollen assemblage results in the valuable characterisation of interactions at varying hierarchical levels throughout a plant-pollinator community [117]. To date, of the studies that have identified resource partitioning within plant-pollinator networks using DNA metabarcoding, all have found that generalised networks or species are made up of specialised individuals [44,84,115,118]. This presents a promising area of research to further investigate the levels of specialisation and generalisation exhibited by pollinators.…”
Section: How Are Resources Partitioned Between Species and Individual...mentioning
confidence: 99%
“…The ability to identify an individual's entire pollen assemblage results in the valuable characterisation of interactions at varying hierarchical levels throughout a plantpollinator community [104]. To date, of the studies that have identified resource partitioning within plant-pollinator networks using DNA metabarcoding, all have found that generalised networks or species are made up of specialised individuals [39,66,68,105]. This presents a promising area of research to further investigate the levels of specialisation and generalisation exhibited by pollinators.…”
Section: How Are Resources Partitioned Between Species and Individuals In Plant-pollinator Network?mentioning
confidence: 99%